Better off without the euro? Structural VAR assessment of European monetary policy - Jan Philipp Fritsche; Patrick Christian Harms (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Modern OCA theory has developed different conclusions on when forming a currency union is beneficial. An important pragmatic question in this context is: Did delegating monetary policy to the ECB increase stress in the individual euro area countries? An SVAR analysis reveals that monetary stress has declined more in the euro area than in the euro areas' doppelganger. The synthetic doppelganger is composed of other OECD countries. This result is independent of the identification strategy (sign restrictions/heteroskedasticity/Cholesky). The results can be rationalized by more formalized central banking and the euro becoming a dominant currency.
Keywords: C32; E42; E52; F45; 330; Economic and Monetary Union; ECB; euro area; structural vector autoregressions; monetary policy stress; sign restrictions; heteroskedasticity; dominant currency